Testing, not modelling, the impact of cohesion support: A theoretical framework and some preliminary results for the Spanish regions - Angel de la Fuente (Center for Economic Studies and ifo Institute (CESifo), 2010)
This paper develops a simple model that can be used to estimate the effectiveness of Cohesion expenditure relative to similar but unsubsidized projects, thereby making it possible to explicitly test an important assumption that is often implicit in estimates of the impact of Cohesion policies. Some preliminary results are reported for the case of infrastructure investment in the Spanish regions.
Keywords: R58; H54; 330; Cohesion policy effectiveness; structural fund evaluation; EU-Strukturfonds; EU-Regionalfonds; Infrastrukturinvestition; Wirkungsanalyse; Regionale Entwicklung; Spanien